Effective Vertical Transport of Particulate Organic Carbon in the Western North Pacific Subarctic Region - Honda, Makio C. (Frontiers in Earth Science, 2020)
To quantify the biological carbon pump in the western North Pacific, a comparative biogeochemistry study of subarctic-eutrophic and subtropical-oligotrophic regions, the K2S1 project, was conducted. This study used data collected during the K2S1 project to re-examine the biological carbon pump in subarctic and subtropical regions of the northwestern Pacific with a focus on the factors governing the attenuation of the downward fluxes of particulate organic carbon (POC). Seasonal and time-series observations made during the K2S1 project revealed that primary productivity and the POC flux in the upper 200 m at subtropical-oligotrophic station S1 were comparable tothose at subarctic-eutrophic station K2, but the POC flux at a depth of ~5000 m at K2 was 2–3 times that at S1. Based on these observations, the index of vertical attenuation (exponent b of the “Martin curve”) was estimated to be 0.64 at K2 and 0.90 at S1. The downward transport of POC was therefore more efficient at the subarctic station than at the subtropical station. Sinking particles were ballasted mainly by biogenic opal (Opal) at K2 and by CaCO3 at S1. The results of a multiple linear regression analysis of sediment trap data indicated that among potential ballast materials, Opal was most strongly correlated with POC at K2. Thus, Opal might contribute to the more effective vertical transport of POC in the western North Pacific Subarctic region. In addition, lower water temperatures and dissolved oxygen concentrations in the twilight zone (200–1000 m depth) at K2 likely slowed microbial decomposition of organic carbon and may also have contributed to the smaller attenuation of the downward POC flux. However, seasonal observations indicated that the carbon demand of zooplankton (prokaryotes) in the water column at K2 was ~2.5 (1.5) times that at S1. These results were inconsistent with the lower rate of attenuation of POC fluxes at K2. Moreover, the carbon demand at the two stations inferred from the POC fluxes and the carbon fluxes associated with diurnal migration by zooplankton exceeded the carbon supply, especially at K2. Other sources of carbon, such as slowly sinking and suspended POC, might account for this mismatch.